2015
DOI: 10.1002/psp.1934
|View full text |Cite
|
Sign up to set email alerts
|

Geo‐cultural Origin and Economic Incorporation of High‐skilled Immigrants in Israel

Abstract: The present study focuses on differential modes of economic incorporation and economic success of highly skilled immigrants in Israel. Data were obtained from the 2009–2011 Labor Force and Income Surveys. The analysis pertains to recent immigrants aged 25–64 years who attained academic education prior to migration. Three major geo‐cultural groups of immigrants are compared with Israeli‐born. The groups are as follows: Europe and the Americas, the Former Soviet Union, and Asia and Africa. The multivariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
4
13
0
Order By: Relevance
“…Length of residency in the host country improves socioeconomic outcomes of skilled immigrants. With the passage of time, immigrants gain knowledge of the society, acquire country-specific skills, and are better equipped to compete for higher paying jobs (Beckhusen et al, 2013 ; Bodankin & Semyonov, 2016 ). Older professionals adapt better socioeconomically, as they have a higher amount of human capital and experience (Bodankin & Semyonov, 2016 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 4 more Smart Citations
“…Length of residency in the host country improves socioeconomic outcomes of skilled immigrants. With the passage of time, immigrants gain knowledge of the society, acquire country-specific skills, and are better equipped to compete for higher paying jobs (Beckhusen et al, 2013 ; Bodankin & Semyonov, 2016 ). Older professionals adapt better socioeconomically, as they have a higher amount of human capital and experience (Bodankin & Semyonov, 2016 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…With the passage of time, immigrants gain knowledge of the society, acquire country-specific skills, and are better equipped to compete for higher paying jobs (Beckhusen et al, 2013 ; Bodankin & Semyonov, 2016 ). Older professionals adapt better socioeconomically, as they have a higher amount of human capital and experience (Bodankin & Semyonov, 2016 ). Prior research found regional variations in socioeconomic outcomes, with immigrants residing in central cities having higher socioeconomic status than others (Bodankin & Semyonov, 2016 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations